INFORMATION ASYMMETRY AND MASS APPRAISAL - Gdakowicz, Anna; Putek-Szeląg, Ewa; Kuźmiński, Wojciech (Metody Ilościowe w Badaniach Ekonomicznych, 2019)
In the article, we propose a new method of valuation based on market value coefficients which we have called the Szczecin algorithm of mass appraisal (SAMWN). This algorithm takes into account the idea that it is possible to measure the effects of both immeasurable and measurable variables which have not been directly included in the valuation. It is therefore a proposal to solve the problem of asymmetry of information in the mass appraisal. The article discusses the procedure of estimating the property value in the process of mass appraisal, in which the attribute related to location and fashion is not included a priori.